Asuhan Keperawatan pada Pasien Gastritis di RS Wonolangan Probolinggo: Studi Kasus - Tri Cahyo Sepdianto; Andi Hayyun Abiddin; Titik Kurnia (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Background: Gastritis is a state of inflammation of the gastric mucosa that can be acute and chronic due to the inattention of sufferers to health, one of which is the application of an unhealthy lifestyle. Aim: Identify an overview of nursing care case studies in patients with gastritis problems at Wonolangan Probolinggo Hospital. Method: This qualitative research uses a case study design specifically designed to study in detail and depth about a case and include various sources of information. Results: Studies that have been done on Mr. A found that nutritional deficits are associated with nausea. After the act of foster care, the nausea experienced by Mr. A was reduced marked by an increase in his appetite of Mr. A. Conclusion: The problem of nursing deficit nutrition has been resolved. Motivation and health education are needed for people with gastritis, including maintaining oral hygiene, eating with small but frequent portions, and maintaining a good diet